sid1, a gene initiating siderophore biosynthesis in Ustilago maydis: molecular characterization, regulation by iron, and role in phytopathogenicity. - Mei, B (1993)
Iron uptake in Ustilago maydis is mediated by production of extracellular hydroxamate siderophores. L-Or-nithine N5-oxygenase catalyzes hydroxylation of L-ornithine, which is the first committed step of ferrichrome and ferrichrome A biosynthesis in U. maydis. We have characterized sid1, a gene coding for this enzyme, by complementation in trans, gene disruption, and DNA sequence analysis. A comparison of genomic DNA and cDNA sequences has shown that the gene is interrupted by three introns. The putative amino acid sequence revealed similarity with Escherichia coli lysine N6-hydroxylase, which catalyzes the hydroxylation of lysine, the first step in biosynthesis of aerobactin. Two transcription initiation points have been determined, both by PCR amplification of the 5' end of the mRNA and by primer extension. A 2.3-kb transcript which accumulates in cells grown under low iron conditions was detected by Northern hybridization. A less abundant 2.7-kb transcript was observed in cells grown in iron-containing medium. By contrast, constitutive accumulation of the 2.3-kb transcript was observed in a mutant carrying a disruption of urbs1, a gene involved in regulation of siderophore biosynthesis. Analysis of the pathogenicity of mutants carrying a null allele of sid1 suggests that the biosynthetic pathway of siderophores does not play an essential role in the infection of maize by U. maydis.